Efficiency Analysis of the 946–P-1–B Centrifugal Pump in PT Installation and Shipment Area. Pertamina Refinery Unit II Production Sungai Pakning - Abdurrahman, Ridwan; Romadhani, Rizki Fitriadi (Department of Mechanical Engineering, Universitas Andalas, 2024)
Centrifugal pumps are a type of pump that is widely used in various industrial applications to convey liquids. This article presents a comprehensive review of centrifugal pumps, including working principles, main components, pump power, and pump efficiency. Centrifugal pumps operate on the principle of converting kinetic energy into hydraulic energy to move fluids through a pipe system. The main components include the impeller, casing, shaft, and seal. There are several types of centrifugal pumps, including single-stage and multi-stage pumps. Centrifugal pump applications include use in the chemical industry, water treatment, agriculture, firefighting, and more. The advantages of centrifugal pumps include compact size, high efficiency, and the ability to handle fluids of various viscosities. By understanding the basic principles and applications of centrifugal pumps, users can optimize the performance of their fluid flow systems efficiently and reliably. The 946-P-1B pump is a pump used for crude feed pumps or can be said to transfer crude oil from the tank to the distillation unit. Based on analysis of the calculation data, it can be concluded that the efficiency of the 946-P-1 B pump has a range of between 47% and 55%. This efficiency describes the level of the pump's ability to convert hydrolysis power into power on the pump shaft. It was found that pump efficiency tends to be directly proportional to the power on the pump shaft; The higher the pump shaft power (Pout), the pump efficiency also tends to increase.